Uncovering Gas Insulated Substation Transient Behaviours Using the Equivalent Cable Model - Nouri, Hassan; Muresan, Alexandru; Czumbi, Levente; Micu, Dan (Journal of Electronics and Electrical Engineering, 2023)
An improved circuit theory approach is proposed for verification of data obtained with the Electro-Magnetic Field (EMF) theory for the study of Gas Insulated Substations (GIS) transient behaviours. The improved circuit theory utilises the concept of an equivalent cable model. The proposed equivalent cable model reduces time and eliminates costs associated with experimentation, which in some cases is not feasible. The degree of accuracy of the proposed model when used as a benchmark for verification purposes is also reported.